Medication adherence and patient satisfaction among low socioeconomic hypertensive older people visiting a secondary care public hospital in south India - Sivasankaran Ponnusankar, Hunsur Nagendra Vishwas, Kathalat Anjali, Siva Manoj Kumar, Viswanathan Balasubramaniam (Journal of Applied Pharmaceutical Science, 2022)
This study aimed to assess the medication adherence and treatment satisfaction in ageing hypertensive patients. It also evaluated the prevalence and potential predictors of nonadherence. The present observational study was conducted at a public secondary care hospital. Hypertensive patients of either sex aged >60 years visiting outpatient departments and hospital pharmacies were recruited into the study. Adherence and treatment satisfaction in the study population was measured using the Morisky Medication Adherence Scale and the Medication Interview Satisfaction Scale (MISS-21), respectively. A total of 202 aged hypertensive patients participated in the study. Majority of the study population had a low socioeconomic status and were within the age group of 60–65 years. Most of the patients reported good treatment satisfaction in all the domains of MISS-21. The prevalence of nonadherence (low to medium) was found to be 61.38%. Upon execution of bivariate analysis, elevated blood pressure, polypharmacy, and nonvegetarian diet were identified as predictors for nonadherence in the study population (p < 0.05). Multiple factors, like patient’s mental status, health literacy, comorbidities, and drug-related problems, affect medication adherence behavior. Geriatric patients need to be specially addressed at hospitals regarding the advantages of treatment adherence. In the Indian set-up, there is an increased responsibility on all the healthcare professionals when dealing with ageing patients with chronic diseases.
Keywords: Ageing population, hypertension, India, medication adherence, treatment satisfaction